Perception towards mandatory continuing professional development programme among nurses working at University of Nigeria Teaching Hospital, Enugu-Nigeria. (2019) - Ingwu, Justin Agorye; Efekalam, Jennifer; Nwaneri, Ada; Ohaeri, Beatrice; Israel, Chidinma; Chikeme, Paulina; Madu, Obiageli; Opara, Hope; Omotola, Ngozi
Abstract: Background: With today's rapidly changing world, professional competence needs to be maintained, and it is imperative that nurses at all levels of the healthcare system show interest in life-long continuing professional education. The aim of the study was to examine the perception towards mandatory continuing professional development programme (MCPDP) among nurses working in University of Nigeria Teaching hospital, Enugu – Nigeria. Methods: A cross sectional descriptive survey design was used for the study and convenience sampling was used to select 244 respondents. An adopted questionnaire was used to collect data and data was analyzed with IBM version 21. Result: Result revealed that mean score of 3.5 ± 6.7 of nurses opined that the programme is the act of using learning to improve nursing care, also a mean score of 3.4 ± 8.8 affirmed that MCPDP involves keeping up to date with knowledge and skills, while score of 3.5 ± 10.6 agreed that it is a learning activity after basic formal education, 100% of the nurses participate in the programme to develop proficiency necessary to meet patients' expectations, while 96.8% were of the opinion to renew their licenses. The major barrier faced by nurses was lack of financial support to fund the programme at the desirable time with score of 3.6 ± 10.6. Conclusion: It was concluded that policy makers should aim at eliminating the barriers faced by nurses and nurses should continue to explore ways to protect public interest in relation to the practice of nursing in Nigeria through update programme.